2008
DOI: 10.1007/s10350-008-9212-9
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis-Associated Colorectal Cancer is Frequently Associated with the Microsatellite Instability Pathway

Abstract: The carcinogenesis process in ulcerative colitis-associated colorectal cancer was closely associated with the microsatellite instability pathway through TGFbetaRII mutation by a dysfunction of the mismatch repair system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…Previous studies have demonstrated that genetic instability occurs during IBD tumorigenesis and that the MSI phenomenon is identified in IBD, even in the regenerative nondysplastic mucosa of UC patients. [24][25][26] Our current study found that 9.6% of UC-associated adenocarcinomas and 9% of pouch adenocarcinomas had complete loss of at least 1 MMR protein, in line with previous reports that MSI-H is found in only a small proportion of IBD-associated adenocarcinomas. 10,[27][28][29] Collectively, existing evidence supports that loss of MMR protein(s) and MSI-H contributes to the tumorigenesis of about 15% of pouch and UC-associated adenocarcinomas.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have demonstrated that genetic instability occurs during IBD tumorigenesis and that the MSI phenomenon is identified in IBD, even in the regenerative nondysplastic mucosa of UC patients. [24][25][26] Our current study found that 9.6% of UC-associated adenocarcinomas and 9% of pouch adenocarcinomas had complete loss of at least 1 MMR protein, in line with previous reports that MSI-H is found in only a small proportion of IBD-associated adenocarcinomas. 10,[27][28][29] Collectively, existing evidence supports that loss of MMR protein(s) and MSI-H contributes to the tumorigenesis of about 15% of pouch and UC-associated adenocarcinomas.…”
Section: Discussionsupporting
confidence: 93%
“…Microsatellite instability (MSI) and loss of heterozygosity (LOH) were analysed by PCR-LOH/MSI assay, as previously reported (Fujiwara et al, 2008). A 6 ml aliquot of reaction mixture was formulated using 0.4 ml of DNA extracted from normal epithelium, primary tumour, OCUM-12, and OCUM-12/Hypo cells.…”
Section: Pcr-loh/msi Assaymentioning
confidence: 99%
“…Although the same pathogenetic and molecular features detected in patients with sporadic CRC such as microsatellite instability, chromosome instability, loss of heterozygosity, and DNA hypermethylation are also found in patients with colitis-associated cancers, the molecular pathway leading to CRC in IBD appears to differ significantly from the classical sporadic adenoma-to-CRC sequence, given the fact that these cancers appear to arise from either flat dysplastic tissue or dysplasia-associated lesions or masses (nonadenoma-like raised lesions or dysplasia-associated lesion or mass) [14,15,16,17,18]. IBD-associated carcinogenesis follows progression from an absence of dysplasia to indefinite dysplasia, then to LGD, on to HGD, and ultimately to invasive CRC.…”
Section: Molecular Mechanisms Of Ibd-associated Colon Carcinogenesismentioning
confidence: 99%